Palliation Versus Dialysis for End-Stage Renal Disease in the Oldest Old: What are the Considerations?. (7th October 2017) - Walton, Lyle S; Shumer, Gregory D; Thorsteinsdottir, Björg; Suh, Theodore; Swetz, Keith M
As the US population continues to age, new cases of end-stage renal disease (ESRD) in individuals, aged 85 years or older (the oldest old), are increasing. Many patients who begin hemodialysis despite questionable benefit may struggle with high symptom burden and rapid functional decline. This article reviews the history regarding the funding and development of the Medicare ESRD program, reviews current approaches to the oldest old with ESRD, and considers strategies to improve the management approach of this vulnerable population.